2006
DOI: 10.2460/ajvr.67.7.1136
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ketamine, diazepam, and their combination on intraocular pressures in clinically normal dogs

Abstract: Compared with baseline values and values obtained from dogs in the SAL group, ketamine administered at a dose of 5 mg/kg, IV, caused a significant and clinically important increase in IOP in dogs in which premedication was not administered. Ketamine should not be used in dogs with corneal trauma or glaucoma or in those undergoing intraocular surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
64
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 11 publications
1
64
6
Order By: Relevance
“…14 Although there are reports of mild and nonsignificant IOP increases as a result of ketamine treatment in some veterinary species, 16,17 the drug typically causes significant increases in IOP in dogs (38%), cats (10%), and rabbits (198%). [18][19][20] Failure of the xylazine-guaifenesin protocol to prevent ketamine-induced increases in IOP further suggests that it may not be possible to prevent ketamineinduced extraocular muscle contraction in horses even following administration of xylazine and high doses of guaifenesin known to cause muscle relaxation.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…14 Although there are reports of mild and nonsignificant IOP increases as a result of ketamine treatment in some veterinary species, 16,17 the drug typically causes significant increases in IOP in dogs (38%), cats (10%), and rabbits (198%). [18][19][20] Failure of the xylazine-guaifenesin protocol to prevent ketamine-induced increases in IOP further suggests that it may not be possible to prevent ketamineinduced extraocular muscle contraction in horses even following administration of xylazine and high doses of guaifenesin known to cause muscle relaxation.…”
Section: Discussionmentioning
confidence: 95%
“…14 In dogs, ketamine has been associated with mild and nonsignificant increases in IOP. 16,17 However, other studies [18][19][20] in dogs, cats, and rabbits have revealed significant increases in IOP following ketamine administration. The postulated mechanisms for the increase in IOP associated with ketamine involve an increase in choroidal blood flow as a result of an increase in blood pressure and also an increase in extraocular muscle tone.…”
mentioning
confidence: 98%
“…In dogs and rabbits, ketamine-diazepam, given intravenously (IV) and IM respectively, increases IOP within 20 minutes after injection (HOFMEISTER et al, 2006;MOGHADDASSI, 2010). However, found that in dogs the combination of ketamine with midazolam in dogs did not change in IOP after 20 minutes of administration.…”
Section: Discussionmentioning
confidence: 98%
“…The effects of dissociative anesthetic combinations on IOP have been studied in dogs, horses, and rabbits (HOFMEISTER et al, 2006;TRIM;COLBERN;MARTIN, 1985;MOGHADDASSI, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation